2018
DOI: 10.1177/1721727x18757262
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR-9 polymorphisms with the development of gastroduodenal ulcer: A hospital-based study in a Chinese cohort

Abstract: Helicobacter pylori infections have been one of the major factors associated with gastroduodenal ulcer. Toll-like receptors (TLRs) of human recognize mycobacterium-induced immune response and protect subjects from disease pathogenesis. Variants in TLR genes are believed to influence immune responses to H. pylori and clinical severity. TLR-9 polymorphisms have been associated with susceptibility to gastroduodenal ulcer in different populations. In this study, we investigate the role of common TLR-9 variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Minor allele homozygotes (TT) were associated with a lower risk of H. pylori infection when compared to their major allele homozygotes (CC), (adjusted OR =0.38, 95% CI, 0.17-0.85, p=0.02 for the rs187084 CC genotype 38 . Similarly, Xu et al investigated the role of TLR-9 polymorphisms (C-1237T, C-1486T, and G+2848A) in susceptibility or resistance to the development of gastroduodenal ulcer in a Chinese cohort and found that TC genotype of TLR-9 C-1486T SNP was more common (48 %) in control group compared to other genotypes which agreed with our results 39 .…”
Section: Discussionsupporting
confidence: 89%
“…Minor allele homozygotes (TT) were associated with a lower risk of H. pylori infection when compared to their major allele homozygotes (CC), (adjusted OR =0.38, 95% CI, 0.17-0.85, p=0.02 for the rs187084 CC genotype 38 . Similarly, Xu et al investigated the role of TLR-9 polymorphisms (C-1237T, C-1486T, and G+2848A) in susceptibility or resistance to the development of gastroduodenal ulcer in a Chinese cohort and found that TC genotype of TLR-9 C-1486T SNP was more common (48 %) in control group compared to other genotypes which agreed with our results 39 .…”
Section: Discussionsupporting
confidence: 89%
“…This state of chronic gastritis can promote the development of gastric cancer, which can explain our findings. In a more recent study, Xu and his colleagues (2018) have reported a significant association between the CC genotype of TLR9 -1486T/C and increased expression of TNF-α and IL-1β cytokines, affecting the infection outcome. Therefore, such SNP can modify the TLR9 expression, affect the pathogenesis of H. pylori infection and increase the risk of gastric cancer ( Wang et al 2013 ).…”
Section: Discussionmentioning
confidence: 95%